Effects of early intervention in neuromyelitis optica spectrum disorder patients with seropositive AQP4 antibodies - Xue, Binbin; Li, Jia; Xie, Dewei; Weng, Yiyun; Zhang, Xu (Frontiers in Immunology, 2024)
BackgroundThe impact of early intervention with immunosuppressive treatment (IST) in anti-Aquaporin4-antibody (AQP4-ab) seropositive neuromyelitis optica spectrum disorder (NMOSD) has not been thoroughly evaluated.ObjectiveThis study aims to assess the effects of early IST intervention in patients with NMOSD.MethodsThis retrospective cohort study included 174 treatments from 137 NMOSD patients seropositive for AQP4-antibody, treated with ISTs such as rituximab, mycophenolate mofetil, azathioprine, or tacrolimus. Multiple statistical analyses, including regression discontinuity design (RDD), kaplan-meier analyze, Cox proportional hazards regression model, were employed to evaluate the effects of early IST intervention on annualized relapse rate (ARR) change, Expanded Disability Status Scale (EDSS) change, and time to next relapse.ResultsA total of 174 treatments from 137 patients were analyzed. Patients exhibited significant improvement in ARR[1.95 vs.0, IQR (0.70-6.0 vs. 0-0.42), p<0.001] and EDSS [3.0 vs. 2.5, IQR (2.0-4.0 vs. 1.0-3.0) p<0.001]after IST, although the ARR change was not significant in patients treated with TAC. Early IST initiation was associated with greater improvements in both ARR and EDSS compared to later initiation. RDD analysis demonstrated a time-dependent effect of ARR-change, indicating greater efficacy with early IST intervention.ConclusionsEarly intervention with ISTs in AQP4-antibody-positive NMOSD patients is associated with better outcomes in terms of reducing relapse rate and improving disability. These findings underscore the importance of early treatment in NMOSD.